Hubungan Sanitasi Jamban dan Air Bersih dengan Kejadian Diare Pada Balita di Kelurahan Terjun Kecamatan Medan Marelan Kota Medan Tahun 2014 - Meithyra Melviana Simatupang; surya dharma; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Diarrhea is a communicable disease that caused by virus, bacteria or protozoa. Diarrhea can cause malnutrition, dehidration, even mortality. Therefore diarrhea must be prevented especially for susceptible people like children under five years old. One of the areas in Kota Medan, which have the incident of diarrhea among children under five years old relatively high is Kelurahan Terjun. The purpose of this study is to analyze the correlation between latrine sanitation and clean water resources and the incident of diarrhea among children under five years old at Kelurahan Terjun. Then to find out the condition of latrine sanitation, water and the incident of diarrhea at this area. This is an analitic research with a cross sectional design. The population is all of children under five years old at three Lingkungan that has the most number of children under five years old as many as 492 people. The samples of 30 children under five years old was taken by systematic random sampling technique. Data was collected by interviewing mother using the questionnaire and observation sheet. Data was analyzed using exact fisher test (p=0,05). The research results showed the correlation between latrine sanitation especially the usage of latrine and water with incident of diarrhea among children under five year at Kelurahan Terjun. The correlation was proved by the probabilities number of usage of latrine (p = 0,015) and bacteriological quality of water (p = 0,002) are less than 0,05. The conclusion of this study is not eligible latrine sanitation causing water resources contaminated by feces. Therefore the improvement of latrine sanitation and water treatment is necessary before use of drinking water or food processing to prevent diarrhea infected among children under five years old. Keywords : Diarrhea, Children Under Five Years Old, Latrine Sanitation, Water